Examination of nutrient reaction of winter wheat after sunflower forecrop - Szilágyi, Gergely (Acta Agraria Debreceniensis, 2016)
We tested the fertilizer reaction of four different winter wheat varieties in three different crop years, on chernozem soil, in long-term experiment. We examined the optimum fertilizer requirements and the maximum yield of the varieties. According to our results there were significant differences among the years: the yield of the winter wheat varieties changed between 1.4–6.1 t ha-1 in 2013, 3.8–8.6 t ha-1 in 2014 and 3.2–8.6 t ha-1 in 2015. The yield increasing effect of fertilization was significantly different in the tested years. The optimum level of fertilization was determined by, besides the genetic differences among the varieties, the crop year and the extent of fertilization. In milder winter months, due to the higher average temperatures, yields of winter wheat increased compared to an average crop year.